Markov processes, Gaussian processes, and local times - Marcus, Michael B. (Cambridge studies in advanced mathematics, 2006)
Two foremost researchers present important advances in stochastic process theory by linking well understood (Gaussian) and less well understood (Markov) classes of processes. It builds to this material through 'mini-courses' on the relevant ingredients, which assume only measure-theoretic probability. This original, readable book is for researchers and advanced graduate students.